Pengembangan Perencanaan Pembelajaran Terhadap Kualitas Mengajar Guru - Safran Safran; Annisa Balqis; Putri Aulia Sitorus; Salsabila Putri Wibowo; Nur Hafni Bahri (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Learning planning is a product that an educator must fulfill before the learning process takes place. But the reality is from the research result Previously, educators designed learning plans only to fulfill school administration as a requirement for supervision or assessment. The purpose of this researc is to strengthen the argument by combining the results of previous research that learning planning must be carried out by every individual educator to improve the quality of educators. This is also the basis for researchers conducting research related to learning planning. research methods used in this research is the literature study research method. Results research is learning planning which is the spearhead of success achieving learning objectives, and improving the quality of educators in terms of competency pedagogical.